Leadership in the Antipodes : findings, implications and a leader profile - Parry, Ken W.; Victoria University of Wellington. Institute of Policy Studies; Victoria University of Wellington. Centre for the Study of Leadership (Wellington, NZ : Institute of Policy Studies and the Centre for the Study of Leadership, 2001)
"This book brings together leadership research conducted in Australasia in the last years of the 20th century... The contributors are from a range of disciplines and represent New Zealand and Australia equally. They address issues of organisational or managerial leadership mainly, but the implications for the leadership of and within society are also tapped." -- book cover.
Includes bibliographical references.
Keywords: Leadership -- Research; Leadership -- New Zealand; Executive ability -- New Zealand; Organizational effectiveness -- New Zealand